2017
DOI: 10.3171/2016.9.jns161080
|View full text |Cite
|
Sign up to set email alerts
|

Utility of MRI-based disproportionately enlarged subarachnoid space hydrocephalus scoring for predicting prognosis after surgery for idiopathic normal pressure hydrocephalus: clinical research

Abstract: OBJECTIVE The presence of disproportionately enlarged subarachnoid space hydrocephalus (DESH) on brain imaging is a recognized finding of idiopathic normal pressure hydrocephalus (iNPH), but the features of DESH can vary across patients. The aim of this study was to evaluate the utility of MRI-based DESH scoring for predicting prognosis after surgery. METHODS In this single-center, retrospective cohort study, the DESH score was determined by consensus between a group of neurosurgeons, neurologists, and a neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
39
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 24 publications
3
39
0
2
Order By: Relevance
“…Specifically, a small callosal angle or the finding of DESH was not associated with a favorable outcome. The lack of correlation between morphologic MR imaging markers and postoperative improvement corroborates some earlier studies 9,12,25 and contradicts other publications that have reported significant associations between postoperative improvement and the presence of a narrow callosal angle, 16 the DESH phenomenon, 15,16 and dilation of the temporal horns. 8 A possible explanation for the different results regarding the predictive value of morphologic imaging markers reported here compared with many earlier studies could be the selection of patients.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Specifically, a small callosal angle or the finding of DESH was not associated with a favorable outcome. The lack of correlation between morphologic MR imaging markers and postoperative improvement corroborates some earlier studies 9,12,25 and contradicts other publications that have reported significant associations between postoperative improvement and the presence of a narrow callosal angle, 16 the DESH phenomenon, 15,16 and dilation of the temporal horns. 8 A possible explanation for the different results regarding the predictive value of morphologic imaging markers reported here compared with many earlier studies could be the selection of patients.…”
Section: Discussionsupporting
confidence: 78%
“…Many of the previous studies have used the modified Rankin Scale, which was developed for use in patients with stroke and does not measure symptom severity in iNPH but instead provides a general measure of disability. 27 Other groups have applied outcome scales based on ordinal or nominal ratings, 8,10,15 making a direct comparison with the results presented here more difficult. To maximize the sensitivity and validity of results, one should use quantitative outcome measures if possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some recent studies attempted to evaluate DESH quantitatively. MRI-based DESH score, one of the quantitative analyses, is useful to predict shunt responsiveness in iNPH patients [11]. DESH score is composed of the following factors, each scored from 0 to 2 (maximum score 10): ventriculomegaly, dilated sylvian fissures, tight high convexity, acute callosal angle (CA) and focal sulcal dilation (Table S1).…”
Section: Introductionmentioning
confidence: 99%
“…DESH score is composed of the following factors, each scored from 0 to 2 (maximum score 10): ventriculomegaly, dilated sylvian fissures, tight high convexity, acute callosal angle (CA) and focal sulcal dilation (Table S1). The literature suggests that a high DESH score has a positive predictive value related to responsiveness to shunt operation [11].…”
Section: Introductionmentioning
confidence: 99%